Descarga em barreira dielétrica: construção de um reator DBD e caracterização mediante análises ópticas e elétricas do plasma produzido - Souza, Ivan Alves de (2013)
The plasma produced by Dielectric Barrier Discharge (DBD) is a promising technique for producing plasma in atmospheric pressure and has been highlighted in several areas, especially in biomedical and textile industry, this is due to the fact that the plasma generated by DBD not reaches high temperatures, enabling use it for thermally sensitive materials. But still it is necessary the development of research related to understanding of the chemical, physical and biological interaction between the non-thermal plasma at atmospheric pressure with cells, tissues, organs and organisms. This work proposes to develop equipment DBD and characterize it in order to obtain a better understanding of the process parameters of plasma production and how it behaves under the parameters adopted in the process, such as distance, frequency and voltage applied between electrodes. For this purpose two techniques were used to characterize distinct from each other. The first was the method of Lissajous figures, this technique is quite effective and accurately for complete electrical characterization equipment DBD. The second technique used was Optical Emission Spectroscopy (EEO) very effective tool for the diagnosis of plasma with it being possible to identify the excited species present in the plasma produced. Finally comparing the data obtained by the two techniques was possible to identify a set of parameters that optimize the production when combined DBD plasma atmosphere in the equipment was built precisely in this condition 0.5mm-15kV 600Hz, giving way for further work